2022
DOI: 10.48550/arxiv.2205.01120
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Viable quark-lepton Yukawa ratios and nucleon decay predictions in $SU(5)$ GUTs with type-II seesaw

Abstract: We investigate the viability of predictive schemes for quark-lepton Yukawa ratios and nucleon decay in non-supersymmetric SU(5) Grand Unified Theories (GUTs) where neutrino masses are generated by a type II seesaw mechanism. The scalar sector of the considered scenario contains 5-, 24-and 45-dimensional representations plus a 15dimensional representation for realising the type II seesaw. Predictions for the ratios of the quark and lepton Yukawa couplings emerge when the relevant entries of the Yukawa matrices … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…With these higher dimensional operators at hand, models similar to the GJ model can be build if the following two conditions are satisfied: (i) the Yukawa matrices should be hierarchical, (ii) the 22-and 33-entry should be dominated by a single GUT operator, a concept which is referred to as single operator dominance [28][29][30]. 1 Following this approach, non-SUSY GUT scenarios in which neutrino masses are generated by a type I or a type II seesaw have been investigated in [27], respectively [45]. For GUT scenarios with a type I seesaw it was shown that the GUT scale ratios y τ /y b = 3/2 and y µ /y s = 9/2 are compatible with the experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…With these higher dimensional operators at hand, models similar to the GJ model can be build if the following two conditions are satisfied: (i) the Yukawa matrices should be hierarchical, (ii) the 22-and 33-entry should be dominated by a single GUT operator, a concept which is referred to as single operator dominance [28][29][30]. 1 Following this approach, non-SUSY GUT scenarios in which neutrino masses are generated by a type I or a type II seesaw have been investigated in [27], respectively [45]. For GUT scenarios with a type I seesaw it was shown that the GUT scale ratios y τ /y b = 3/2 and y µ /y s = 9/2 are compatible with the experimental data.…”
Section: Introductionmentioning
confidence: 99%